Online Gaming and Virtual Property Transactions From an Islamic Perspective - A. Adib Dzulfahmi; Tutik Hamidah (State Islamic University Datokarama Palu, 2025)
This study examines the social conditions of online gaming and the transactions of virtual property within it from an Islamic perspective. Online gaming has become a global phenomenon impacting various aspects of life, including social, economic, and spiritual dimensions. Transactions involving virtual property such as the purchase of accounts, items, or in-game currencies have emerged as a new trend; raising legal questions in Islamic jurisprudence. This research employs a qualitative approach with a normative literature review to analyse the rulings on online gaming and virtual transactions based on the principles of maqashid syariah. The findings indicate that the original ruling on online gaming is mubah (permissible). However, it can shift to makruh (disliked) or haram (prohibited) if it negatively impacts religious obligations, social relationships, or economic responsibilities. Similarly, the trade of virtual property is considered valid and lawful (halal) as long as it meets the pillars and conditions of trade in Islam; such as clarity of the object, utility, and ownership. This study aims to serve as a reference for understanding the social impacts of online gaming and to provide a contextual Islamic legal framework for addressing developments in digital technology.